PENGARUH KEPEMIMPINAN, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT JASAMARGA BALI TOL DI DENPASAR - I Putu Gandi Ginatra (Jurnal Ekonomi & Bisnis JAGADITHA, 2017)
Toll road is one of the alternatives used to overcome the increasing congestion in Indonesia. To manage toll roads is not enough with large funds, but must be supported by intensive, planned and measured form of training for all employees. The purpose of this study is to determine the influence of leadership on employee satisfaction, the influence of motivation on employee satisfaction, the influence of satisfaction on employee performance, the influence of leadership on employee performance, the influence of motivation on the performance of employees of PT. Jasamarga Bali Tol in Denpasar. To answer the purpose of this study then conducted research with a population of 94 employees with positions officer PT. Jasamarga Bali Tol as population. Samples were taken using Census method. Methods of data analysis using descriptive analysis and inferential analysis of PLS. The results showed that leadership have positive and significant impact on employee job satisfaction. Motivation has a positive and significant effect on employee job satisfaction. Leadership has a positive and significant effect on employee performance in Denpasar. Motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant impact on employee performance. The suggestions given need to increase the motivation given by the company to the employees, for example by giving the financial motivation more feasible and non-financial motivation such as awards for employee performance.